The public administration imperative of applying an atrocity prevention lens to COVID-19 responses (2020)
The pandemic is already forcing many individuals, businesses, and governments to rethink much of what they do and how they do it. As such, it presents an opportunity for public administrators to reimagine the criteria they use when designing and implementing programs and policies, and to more actively engage in prevention of identity-based violence. In this contribution, we suggest a new analytical lens to guide public administrators’ decision making, one informed by the theory and practice of mass atrocity prevention. This perspective recognizes that the decisions and actions of public administrators in response to the pandemic will influence whether individual countries and the global community writ large will be at increased risk of mass atrocities or if they will be more resilient and better positioned to prevent such atrocities. The COVID-19 pandemic represents both an imperative and an opportunity to reduce risks of mass atrocities, and public administrators have a vital role to play in this process.